Methodological Issue of Mitochondrial Isolation in Acute-Injury Rat Model: Asphyxia Cardiac Arrest and Resuscitation - Aoki, Tomoaki; Okuma, Yu; Becker, Lance B.; Hayashida, Kei; Shinozaki, Koichiro (Frontiers in Medicine, 2021)
Background: Identification of the mechanisms underlying mitochondrial dysfunction is key to understanding the pathophysiology of acute injuries such as cardiac arrest (CA); however, effective methods for measurement of mitochondrial function associated with mitochondrial isolation have been debated for a long time. This study aimed to evaluate the dysregulation of mitochondrial respiratory function after CA while testing the sampling bias that might be induced by the mitochondrial isolation method. Materials and Methods: Adult rats were subjected to 10-min asphyxia-induced CA. 30 min after resuscitation, the brain and kidney mitochondria from animals in sham and CA groups were isolated (n = 8, each). The mitochondrial quantity, expressed as protein concentration (isolation yields), was determined, and the oxygen consumption rates were measured. ADP-dependent (state-3) and ADP-limited (state-4) respiration activities were compared between the groups. Mitochondrial quantity was evaluated based on citrate synthase (CS) activity and cytochrome c concentration, measured independent of the isolation yields. Results: The state-3 respiration activity and isolation yield in the CA group were significantly lower than those in the sham group (brain, p < 0.01; kidney, p < 0.001). The CS activity was significantly lower in the CA group as compared to that in the sham group (brain, p < 0.01; kidney, p < 0.01). Cytochrome c levels in the CA group showed a similar trend (brain, p = 0.08; kidney, p = 0.25). Conclusions: CA decreased mitochondrial respiration activity and the quantity of mitochondria isolated from the tissues. Owing to the nature of fragmented or damaged mitochondrial membranes caused by acute injury, there is a potential loss of disrupted mitochondria. Thus, it is plausible that the mitochondrial function in the acute-injury model may be underestimated as this loss is not considered.